Clustering analysis and differentiation of lard from palm oil and soybean oil based on n-alkane and triacylglycerides profiles using chemometric analysis - Wasoh, Helmi; Sapian, Nur Ain Syaqirah; Mohammad Fatin, Ahmad Muhsin; Halim, Murni; Abdul Rahman, Nor’Aini; Mohd Sobri, Mohamad Zulfazli; Hashim, Amalia Mohd; Yusof, Mohd Termizi; Pak-Dek, Mohd Sabri; Abdul Manaf, Yanty Noorzianna; Mohd Desa, Mohd Nasir; Mohamad Hamzah, Firdaus (Hibiscus Publisher Enterprise, 2024)
This investigation focused on analyzing lard derived from pig adipose tissue and two different vegetable oils (crude palm oil and soybean oil) through triacylglycerides (TAGs) and n-alkane profiling, employing chemometrics techniques. Unsaponifiable palm and soybean oils were isolated and examined using gas chromatography-mass spectrometry (GC-MS) to assess their nalkane profiles. The identified n-alkane profiles were verified by comparing them with n-alkane standards (nC08–nC27). The experimental design incorporated several multivariate techniques, including Hierarchical Clustering Analysis (HCA), Principal Component Analysis (PCA), Random Forest (RF), and Partial Least Squares-Discriminant Analysis (PLS-DA). According to PLS-DA findings, nC25, nC27, and PPL are suggested as key TAG and n-alkane markers for the clustering analysis of lard from crude palm and soybean oils. These results indicate that further research is necessary to refine and validate these distinctions, especially when using chemometrics techniques